Prolapse repair with and without apical resuspension—Practice patterns among certifying American urologists. Issue 2 (6th November 2015) - Liu, Joceline S.; Nettey, Oluwarotimi; Vo, Amanda X.; Hofer, Matthias D.; Flury, Sarah C.; Kielb, Stephanie J.
Abstract : Aims: To examine surgeon characteristics in certifying urologists performing prolapse surgeries. Anterior compartment prolapse is often associated with apical prolapse, with high rates of recurrence when anterior repair is performed without apical resuspension. Methods: Six‐month case log data of certifying urologists between 2003 and 2013 was obtained from the American Board of Urology (ABU). Cases with a CPT code for common prolapse repairs in females ≥18 years were analyzed. Results: Among 2, 588 urologists logging at least one prolapse surgery and a total of 30, 983 surgeries, 320 (1.0% of all cases) uterosacral ligament suspension, 3, 673 (11.9%) sacrospinous ligament suspension, and 2, 618 (8.4%) abdominal sacrocolpopexy were identified. The remaining 14, 585 cases were logged as anterior repair. 54.7% of anterior repairs did not include apical suspension. The proportion of anterior repairs without apical suspension has decreased from 77.7% in 2004 to 41.4% in 2012 ( P < 0.001). Female subspecialists before 2011 performed anterior repair without apical suspension in 58.5%, versus 70.3% by all others. Since 2011 there has been a decrease in number of anterior repairs without apical suspension, notably in those applying for Female Pelvic Medicine and Reconstructive Surgery (FPMRS) certification (17.1% vs. 30.7% by all other urologists, P < 0.001); nonacademically affiliated urologists are 2.1 times more likely to report anterior repair without apical suspension than academically affiliated colleagues ( P < 0.001). Conclusions: The proportion of prolapse repairs reported as anterior repairs without apical suspension is decreasing, although it remains a substantial portion. Recent log year, FPMRS, and academic affiliation were associated with prolapse repairs addressing apical support. Neurourol. Urodynam. 36:344–348, 2017 . © 2015 Wiley Periodicals, Inc.